A novel higher rotational speed maintaining control for wind power generation systems under unstable wind conditions - Hidehito Matayoshi; Masaya Mitsuhashi; Ryoma Onoe; Toshimitsu Morizane; Masahiro Furukakoi; Tomonobu Senjyu (Green Technologies and Sustainability)
This study proposes the Higher Rotational Speed Maintaining (HRSM) control algorithm that is suitable for large wind speed fluctuations. One of the challenges faced by wind generators is operating with significant wind speed oscillations. A wind generator with a large moment of inertia increases the time constant in rotational speed control and delays the tracking of the optimal operating point. This delay could reduce generated power by up to 40% or more. There are numerous regions in Japan’s inland areas where average wind speeds exceed 6.5 m/s. However, frequent fluctuations in wind speeds make wind power generation challenging. Therefore, this paper proposes a control algorithm suitable for wind turbines operating under unstable wind conditions. Higher rotational speeds are required to convert sudden high wind speeds into higher power output, especially when wind speed oscillations are large. Hence, the proposed algorithm focuses on maintaining the rotational speed during periods of unstable wind conditions to improve generation efficiency. The effectiveness of the proposed control method for wind turbines is verified through numerical simulation results. The novel control algorithm aims to promote the spread of wind turbines in areas with unstable wind conditions by overcoming these disadvantages.